2020
DOI: 10.21203/rs.3.rs-125368/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbapenem Resistance Profiles of Pathogenic Escherichia coli in Uganda

Abstract: Background: Escherichia coli has been implicated as one of the main etiological agents of diarrhea, urinary tract infections, meningitis and septicemia worldwide. The ability to cause diseases is potentiated by presence of virulence factors. The virulence factors influence the capacity of E. coli to infect and colonize different body systems. Thus, pathogenic E. coli are grouped into DEC strains that are mainly clustered in phylogenetic group B1 and A; ExPEC belonging to A, B2 and D. Coexistence of virulence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Furthermore, nine of these 11 isolates belonged to B2 phylogroup and two were from B1 group. Most other studies [ 20 22 , 74 ] showed the predominance of OXA-48 among E . coli isolates, especially B2 isolates.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Furthermore, nine of these 11 isolates belonged to B2 phylogroup and two were from B1 group. Most other studies [ 20 22 , 74 ] showed the predominance of OXA-48 among E . coli isolates, especially B2 isolates.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, nine of these 11 isolates belonged to B2 phylogroup and two were from B1 group. Most other studies [20][21][22]74] showed the predominance of OXA-48 among E. coli isolates, especially B2 isolates. Other studies in Iraq [75] and around the world [44,[76][77][78][79][80][81][82] also revealed the occurrence of different carbapenemase genes among E. coli isolates.…”
Section: Plos Onementioning
confidence: 89%
See 1 more Smart Citation
“…This resistance may be attributed to the presence of resistance intrinsic factors, such as downregulation and mutation of the outer membrane proteins, through which antibiotics diffuse [41][42][43][44]. High prevalence of carbapenem resistance has been reported in Uganda [45][46][47]. Acquisition of carbapenemase encoding genes by Enterobacteriaceae confer resistance to all beta lactam antibiotics [41,45].…”
Section: Discussionmentioning
confidence: 99%
“…However, Mahmoud et al demonstrated that bla OXA-48 and bla KPC genes were detected in 15.5% and 8.8% of the isolates, respectively ( 25 ). Ssekatawa et al from Uganda illustrated that the prevalence of bla OXA-48 , bla VIM , bla IMP , bla KPC , bla NDM genes was 33%, 21%, 16.5%, 14.8%, and 14.8%, respectively ( 32 ).…”
Section: Discussionmentioning
confidence: 99%